1986
DOI: 10.1002/1097-0355(198622)7:2<112::aid-imhj2280070204>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The transactional model of early home intervention

Abstract: This article describes a developmental model for early home intervention and treatment of environmentally and biologically at‐risk infants and their parents: The Transactional Model of Home Intervention. The model identifies the development of both infants and parents as targets of intervention and considers their ongoing interactions or transactions within the family context as the vehicle of intervention. The child and his physical/social environment are conceptualized as actively influencing one another in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Cohort studies showed similar outcomes as RCTs. Barrera & Rosenbaum 41 found some effect of structured home visits on parenting skills among mothers belonging to a high-risk family like broken homes or those with drug problems. However, the children's psychomotor development did not show appreciable changes.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Cohort studies showed similar outcomes as RCTs. Barrera & Rosenbaum 41 found some effect of structured home visits on parenting skills among mothers belonging to a high-risk family like broken homes or those with drug problems. However, the children's psychomotor development did not show appreciable changes.…”
Section: 13mentioning
confidence: 99%
“…However, the studies had a number of limitations that affect the study outcomes and hence the overall results, such as high attrition rate and systematic bias, 44 non-uniform assessment of outcomes across cohorts 42 and poor statistical analysis. 41 Studies related to reading Supplementary Table S3 outlines the studies that assessed the impact of reading interventions.…”
Section: 13mentioning
confidence: 99%